Tri6 Is a Global Transcription Regulator in the Phytopathogen Fusarium graminearum - Nasmith, Charles G.; Walkowiak, Sean; Wang, Li; Leung, Winnie W. Y.; Gong, Yunchen; Johnston, Anne; Harris, Linda J.; Guttman, David S.; Subramaniam, Rajagopal (PLoS pathogens, 2011)
In F. graminearum, the transcriptional regulator Tri6 is encoded within the trichothecene gene cluster and regulates genes involved in the biosynthesis of the secondary metabolite deoxynivalenol (DON). The Tri6 protein with its Cys₂His₂ zinc-finger may also conform to the class of global transcription regulators. This class of global transcriptional regulators mediate various environmental cues and generally responds to the demands of cellular metabolism. To address this issue directly, we sought to find gene targets of Tri6 in F. graminearum grown in optimal nutrient conditions. Chromatin immunoprecipitation followed by Illumina sequencing (ChIP-Seq) revealed that in addition to identifying six genes within the trichothecene gene cluster, Tri1, Tri3, Tri6, Tri7, Tri12 and Tri14, the ChIP-Seq also identified 192 additional targets potentially regulated by Tri6. Functional classification revealed that, among the annotated genes, ∼40% are associated with cellular metabolism and transport and the rest of the target genes fall into the category of signal transduction and gene expression regulation. ChIP-Seq data also revealed Tri6 has the highest affinity toward its own promoter, suggesting that this gene could be subject to self-regulation. Electro mobility shift assays (EMSA) performed on the promoter of Tri6 with purified Tri6 protein identified a minimum binding motif of GTGA repeats as a consensus sequence. Finally, expression profiling of F. graminearum grown under nitrogen-limiting conditions revealed that 49 out of 198 target genes are differentially regulated by Tri6. The identification of potential new targets together with deciphering novel binding sites for Tri6, casts new light into the role of this transcriptional regulator in the overall growth and development of F. graminearum.